Midterm results after arterial switch operation for transposition of the great arteries: a single centre experience - Popov, Aron Frederik (BioMed Central, 2012)
BACKGROUND: The arterial switch operation (ASO) has become the surgical approach of choice for d-transposition of the great arteries (d-TGA). There is, however an increased incidence of midterm and longterm adverse sequelae in some survivors. In order to evaluate operative risk and midterm outcome in this population, we reviewed patients who underwent ASO for TGA at our centre. METHODS: In this retrospective study 52 consecutive patients with TGA who underwent ASO between 04/1991 and 12/1999 were included. To analyze the predictors for mortality and adverse events (coronary stenoses, distortion of the pulmonary arteries, dilatation of the neoaortic root, and aortic regurgitation), a multivariate analysis was performed. The follow-up time was ranged from 1–10 years (mean 5 years, cumulative 260 patient-years). RESULTS: All over mortality rate was 15.4% and was only observed in the early postoperative period till 1994. The predictors for poor operative survival were low APGAR-score, older age at surgery, and necessity of associated surgical procedures. Late re-operations were necessary in 6 patients (13.6%) and included a pulmonary artery patch enlargement due to supravalvular stenosis (n = 3), coronary revascularisation due to coronary stenosis in a coronary anatomy type E, aortic valve replacement due to neoaortic valve regurgitation (n = 2), and patch-plasty of a pulmonary vein due to obstruction (n = 1). The dilatation of neoaortic root was not observed in the follow up. CONCLUSIONS: ASO remains the procedure of choice for TGA with acceptable early and late outcome in terms of overall survival and freedom of reoperation. Although ASO is often complex and may be associated with morbidity, most patients survived without major complications even in a small centre.